The Influence of Flexible Work on Work-Life Balance and Employee Performance in Human Resource Management - Ananda, Ade (Green Publisher Indonesia, 2024)
Work-life balance is one of the important factors that affect employee performance. Employees who have a good work-life balance tend to have better performance. The purpose of this study is to examine the effect of flexible work on work-life balance and employee performance. This research uses quantitative methods with a survey approach. The population of this research is employees who work in companies in Bandung City. The sample of this study was 100 employees selected using purposive sampling technique. The data collection techniques used in this study were questionnaires and literature studies. The data analysis technique used is the regression test using the help of the SPSS program. The results showed that flexible work has a positive influence on work balance and employee performance. Employees who work flexibly tend to have better work balance and performance compared to employees who work conventionally. This is indicated by the questionnaire results which show that employees who work flexibly tend to have more time for family and friends, less stress, and more satisfaction with their jobs.